2019
DOI: 10.1371/journal.pone.0213239
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive measurements of hemodynamic, autonomic and endothelial function as predictors of mortality in sepsis: A prospective cohort study

Abstract: Background and aimSepsis is associated with marked alterations in hemodynamic responses, autonomic dysfunction and impaired vascular function. However, to our knowledge, analysis of noninvasive markers to identify greater risk of death has not yet been investigated. Thus, our aim was to explore the prognostic utility of cardiac output (CO), stroke volume (SV), indices of vagal modulation (RMSSD and SD1), total heart rate variability (HRV) indices and FMD of brachial artery (%FMD), all measured noninvasively, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…An increased square root of the mean of the sum of the squares of differences between adjacent NN intervals (RMSSD) was found in patients who developed septic shock within 6 hours of presentation at the ED (44). Reduced RMSSD has also been shown to predict for 28-day mortality in septic patients presenting at the ED (45). Some prior studies demonstrated that a decreased LF/HF ratio of less than 1.0 may predict severity of illness in septic patients (46,47).…”
Section: Adult Sepsismentioning
confidence: 99%
“…An increased square root of the mean of the sum of the squares of differences between adjacent NN intervals (RMSSD) was found in patients who developed septic shock within 6 hours of presentation at the ED (44). Reduced RMSSD has also been shown to predict for 28-day mortality in septic patients presenting at the ED (45). Some prior studies demonstrated that a decreased LF/HF ratio of less than 1.0 may predict severity of illness in septic patients (46,47).…”
Section: Adult Sepsismentioning
confidence: 99%
“…In this study, we could not show the relationship between HRV parameters and the mortality or severity of sepsis compared with previous studies. 5 , 6 , 7 The limitations to the HRV interpretation as a representative of autonomic regulation in sepsis are considered. First, invasive procedures influence HRV.…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). However, previous studies on HRV with the prediction outcome of sepsis are conflicting 5 , 6 , 7 because (i) the specific clinical features reflected by HRV were unclear (e.g., inflammation, hypoperfusion, and organ dysfunction), and (ii) prior studies included the possibility of modifying the invasive procedure influencing HRV. We believe that clarifying the connection between autonomic regulation and pathophysiology in sepsis offers noninvasive and quick measurements of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…In non-septic patients, Bergström et al found RH-PAT to decrease from admission to day 3 after subarachnoid haemorrhage and identified a significant correlation with mortality [ 26 ]. Furthermore, other methods of accessing reactive hyperaemia such as FMD and peak hyperaemic flow velocity in the brachial artery found promising results regarding the association with mortality in the septic and non-septic critically ill patients admitted to the ICU [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%